Safety protocols for dental care during the COVID-19 pandemic: the experience of a Brazilian hospital service - Alessandra Figueiredo SOUZA; José Alcides Almeida de ARRUDA; Fernanda Pereira Delgado COSTA; Larissa Marques BEMQUERER; Wagner Henriques CASTRO; Felipe Eduardo Baires CAMPOS; Fabiana Maria KAKEHASI; Denise Vieira TRAVASSOS; Tarcília Aparecida SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The coronavirus disease (COVID-19) has been prioritized in relation to other illnesses considered critical, such as cancer, cardiovascular diseases/stroke, diabetes, and autoimmune diseases. The management of patients with these diseases involves dental care to reduce systemic complications caused by odontogenic infections, and/or to treat oral manifestations of systemic comorbidities. In this regard, the dental care of these individuals must be guaranteed during the pandemic. Although a high risk of exposure to and catching of COVID-19 is expected to befall dental professionals, biosafety guidelines reduce the likelihood of infection. Thus, the current scenario poses challenges, and offers decision-making approaches and tools that facilitate the management of individuals with oral manifestations of chronic and/or critical diseases, using hospital-based services. This article presents an overview for hospital service providers who are at the forefront of COVID-19 care, including a secure protocol, and clinical guidelines based on the experience of the Hospital das Clínicas in Belo Horizonte, a public referral service, supported by the Brazilian National Health System.